Narcotic Drugs and Psychotropic Substances in India: A Socio-Legal Appraisal of Enforcement, Policy, and Reform (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The issue of narcotic drugs and psychotropic substances represents one of the most pressing socio-legal challenges in contemporary India. The country, due to its geographical proximity to the “Golden Triangle” and the “Golden Crescent,” faces unique vulnerabilities in trafficking, production, and consumption of drugs. The enactment of the Narcotic Drugs and Psychotropic Substances (NDPS) Act, 1985, marked a watershed moment in India’s legal response, introducing stringent prohibitions, severe penalties, and centralized regulatory control. However, four decades of implementation reveal a paradox: while the law has created a robust enforcement framework, it has often overlooked the socio-economic, public health, and rehabilitative dimensions of drug abuse. This article provides a comprehensive socio-legal appraisal of India’s narcotic drugs regime, tracing its historical evolution, evaluating enforcement challenges, and analysing international perspectives. It argues for a balanced approach that combines strict action against traffickers with humane policies for users, emphasizing prevention, rehabilitation, and reform.